Big data and the welfare state how the information revolution threatens social solidarity - Iversen, Torben 1923-1998; Rehm, Philipp 1977- (Cambridge University Press, 2022)
"While we were writing this book, one of the authors fell ill. The diagnosis required two CAT scans, two MRIs, consultation with an oto-neurologist, an otolaryngologist, and an audiologist, while the treatment required a week in the hospital, a total of 15 hours of surgery carried out by a team of highly-skilled neurosurgeons and an anesthesiologist, with several nurses on hand. Another six weeks of recovery involved physical therapy and multiple checkups. A back-of-the-envelope calculation suggests that the whole episode cost in excess of US$250,000, all of which was paid by a private insurance company, Blue Cross Blue Shield, via a standard occupational insurance plan"--
Keywords: Big Data; Wohlfahrtsstaat; Social security / Political aspects; Big data / Social aspects; Big data / Political aspects; Risk / Sociological aspects; Public welfare; Welfare state; Sécurité sociale / Aspect politique; Données volumineuses / Aspect social; Données volumineuses / Aspect politique; Risque / Aspect sociologique; Aide sociale; État providence; welfare services; POLITICAL SCIENCE / General